2016
DOI: 10.5578/mb.24165
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of Multidrug-Resistant Pathogens Responsible for Complicated Skin and Soft Tissue Infections to Standard Bacteriophage Cocktails

Abstract: Skin and soft tissue infections (SSTIs) may represent a wide clinical spectrum from cellulitis to high-mortality associated necrotizing fasciitis. Limitations in therapy due to the multiple drug resistance, leads to increase in the morbidity and mortality rates, especially in complicated SSTIs such as diabetic foot, decubitus, and surgical wound infections. Therefore, alternative treatment strategies other than antibiotics are needed in appropriate clinical conditions. "Bacteriophage therapy", which is an old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This environmental stress generated from ROS and reactive nitrogen species (RNS), combined with increased secretion of inflammatory mediators and enzyme expression (e.g., collagenase and elastase), causes inflammation and decreases the tensile strength and elasticity of the skin [3]. Also in the antimicrobial domain, the incidence of skin and soft tissue infections is growing as a consequence of increasing bacteria resistance to drugs in a wide clinical spectrum [4].…”
Section: Introductionmentioning
confidence: 99%
“…This environmental stress generated from ROS and reactive nitrogen species (RNS), combined with increased secretion of inflammatory mediators and enzyme expression (e.g., collagenase and elastase), causes inflammation and decreases the tensile strength and elasticity of the skin [3]. Also in the antimicrobial domain, the incidence of skin and soft tissue infections is growing as a consequence of increasing bacteria resistance to drugs in a wide clinical spectrum [4].…”
Section: Introductionmentioning
confidence: 99%
“…A group of scientists from Turkey [ 97 ] has studied in vitro the sensitivity of resistant microorganisms, isolated from patients with complicated infections of soft tissues, to the standard bacteriophage (phage) cocktails. The results demonstrate a high potential of topical bacteriophage therapy in the management of complicated soft tissue infections.…”
Section: Bacteriophages In Treatment Of Burn Patientsmentioning
confidence: 99%
“…Nowadays, the use of bacteriophage as an alternative antibacterial drug against various infectious diseases has been reported. Phage therapy would be suggested as a promising antibacterial alternative, in cases where current antibiotics cannot control infections 19–22 . On the other hand, previous studies in food and water treatment, biocontrol, and care have shown that the future applications of bacteriophages will be clear and promising 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Phage therapy would be suggested as a promising antibacterial alternative, in cases where current antibiotics cannot control infections. [19][20][21][22] On the other hand, previous studies in food and water treatment, biocontrol, and care have shown that the future applications of bacteriophages will be clear and promising. 23,24 So far, numerous lytic phages have been isolated against MDR A. baumannii, which have been used in successful clinical trials.…”
Section: Introductionmentioning
confidence: 99%